Continuous flow technology-a tool for safer oxidation chemistry. Issue 3 (18th January 2022) - Wan, Li; Jiang, Meifen; Cheng, Dang; Liu, Minjie; Chen, Fener
Abstract : The advantages and benefits of continuous flow technology for oxidation chemistry have been illustrated in tube reactors, micro-channel reactors, tube-in-tube reactors and micro-packed bed reactors in the presence of various oxidants. Abstract : The oxidation reaction is one of the most important transformations in synthetic chemistry, allowing for the introduction and modification of various functional groups. Continuous flow chemistry involving the use of channels or tubing to conduct a reaction has received a remarkable amount of attention in academia and industry. The technology provides reduced reaction times, higher selectivities, straightforward scalability, and the possibility to safely use hazardous intermediates and gaseous reactants. This review presents an up-to-date overview of oxidation chemistry using various oxidants in continuous flow microreactors. In addition, the advantages of using molecular oxygen as the most environmentally benign oxidant in photochemistry and biochemistry are discussed.